Efficiency of Medical Laboratories after Quality Standard Introduction: Trend Analysis of EU Countries and Case Study from Slovenia - Nejc Lamovšek; Maja Klun (Central European Public Administration Review)
The evaluation of efficiency and effectiveness in the public sector has a long tradition in literature. The data envelopment analysis (DEA) method is hereby a commonly applied method for examining the efficiency of individual public sector units. It also applies to healthcare; however, research on individual parts of this activity is rare, particularly as regards the evaluation of laboratory-based activity. In this article, the DEA method is used to evaluate the efficiency of biomedical laboratories and the change upon quality standards introduction. This is the first example of verification of a change in technical efficiency in relation to the accreditation of ISO standards. In the article, the analysis of the efficiency of Slovenian medical laboratories is presented in terms of the obtained quality standard; moreover, a comparison of Slovenian medical laboratories and two laboratories from neighbouring countries, Austria and Italy, is provided. The results show that the use of the DEA method and the Malmquist index do not indicate an improvement in the technical efficiency of accredited laboratories but the quality indicators indicate a higher quality of performed work. The comparison of Slovenian and foreign laboratories indicates high technical efficiency of accredited laboratories, as they are the highest-ranked; however, the knowledge of laboratories indicates that there are also other reasons for such a ranking. These research results can be utilised in comparable areas and countries.